Quantitative MS‐Based Proteomics: Comparing the MCF‐7 Cellular Response to Hypoxia and a 2‐Oxoglutarate Analogue. (3rd March 2020) - Bush, Jacob T.; Chan, Mun Chiang; Mohammed, Shabaz; Schofield, Christopher J.
Abstract: The hypoxia‐inducible factors (HIFs) are key transcription factors in determining cellular responses involving alterations in protein levels in response to limited oxygen availability in animal cells. 2‐Oxoglutarate‐dependent oxygenases play key roles in regulating levels of HIF and its transcriptional activity. We describe MS‐based proteomics studies in which we compared the results of subjecting human breast cancer MCF‐7 cells to hypoxia or treating them with a cell‐penetrating derivative (dimethyl N ‐oxalylglycine; DMOG) of the stable 2OG analogue N ‐oxalylglycine. The proteomic results are consistent with reported transcriptomic analyses and support the proposed key roles of 2OG‐dependent HIF prolyl‐ and asparaginyl‐hydroxylases in the hypoxic response. Differences between the data sets for hypoxia and DMOG might reflect context‐dependent effects or HIF‐independent effects of DMOG. Abstract : Coming up for air : We describe MS‐based proteomics studies in which we compared the results of subjecting human breast cancer MCF‐7 cells to hypoxia or treating them with a cell‐penetrating derivative (dimethyl N ‐oxalylglycine) of the stable 2OG analogue N ‐oxalylglycine.